Development of Web-Based Pascal Programming Multimedia at UPT SMK Negeri 2 Sidrap - Ayu Anjeliani; Nurmayanti Lamanna; Muhammad Takdir (Universitas Muhammadiyah Enrekang, 2022)
This study aims to develop web-based Multimedia Pascal Programming in the basic programming subject of TKJ class X UPT SMK Negeri 2 Sidrap. This type of research is research and development (Research and Development / R&D) with a 4D development model that has been developed by Thiagarajan, Semmel and Semmel (1974) which includes the stages of Define, Design, Develop, and Disseminate. Data collection uses observation instruments, interviews, and questionnaires which are then analyzed descriptively quantitatively. The results showed that Pascal Programming multimedia met the valid criteria based on the assessment of media and material validation with an average value of 85.5%. Thus, it can be concluded that multimedia Pascal Programming is declared very suitable for use in limited face-to-face learning UPT SMK Negeri 2 Sidrap.